Compost of peanuts residue and rice straw compost on soil Nitrogen forms and upland rice yield - Sholihah, Anis; Sugianto, Agus; Lestari, Mahayu Woro (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2023)
This study provides an innovation in making compost from rice straw (low quality) mixed with peanut residue (high quality) to improve the quality of rice straw compost. The purpose of this research was to discover the optimum composition of a mixture of peanut residue and straw for mineralization, absorption, and Nitrogen Use Efficiency (NUE) and its effect on upland rice plants. The study was conducted in three stages. The first stage determined the quality of five compost mixtures: C1, C2, C3, C4, and C5. The second phase of testing for cumulative N minerals was performed after 1, 2, 4, and 8 weeks of incubation. The third stage examined the impact of the compost mixture on the growth and yield of upland rice in comparison with two treatments, namely the control and NPK fertilizer. The results showed a similarity in the forms of mineralization, where the cumulative N mineral increased with the addition of peanut residue to the compost mixture. The use of a mixture of peanut residue and rice straw compost increased net mineralization by 37.27% (C5) to 59.48% (C1), N uptake by 49.19% (C5) to 62.95% (C3), and NUE by 15.04% (C4) to 51.48% (C3). A strong relationship was detected between the quality of the compost and the forms of N in the soil, particularly the nitrate content, total N minerals, and N microbial biomass, with correlation coefficients of 0.92, 0.88, and 0.94, respectively. A strong to very strong relationship was detected between N form and N uptake (r = 0.84), plant height (r = 0.79), number of tillers (r = 0.78), yield of rice plants (r = 0.93 (plant total dry weight), and r = 0.76 (grain weight). The optimum N uptake, NUE, and yield of upland rice were shown by C3 treatment of 405.28 mg pot-1, 42.21%, and 6.19 tons ha-1, respectively.